2007
DOI: 10.1200/jco.2006.08.8898
|View full text |Cite|
|
Sign up to set email alerts
|

Phase I Pharmacokinetic and Biologic Correlative Study of Mapatumumab, a Fully Human Monoclonal Antibody With Agonist Activity to Tumor Necrosis Factor–Related Apoptosis-Inducing Ligand Receptor-1

Abstract: Mapatumumab can be administered safely and feasibly at 10 mg/kg IV every 14 days. The absence of severe toxicities and the attainment of plasma mapatumumab concentrations that are active in preclinical models warrant further disease-directed studies of this agent alone and in combination with chemotherapy in a broad array of tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
165
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(177 citation statements)
references
References 11 publications
10
165
0
2
Order By: Relevance
“…Some of them are now under various phases of clinical trials (1)(2)(3)10). The advantages of agonistic mAbs compared with TRAIL include specificity of binding to their target receptor without cross-reactivity with the DcRs, much longer serum half-life, and the crystallizable fragment (Fc)-mediated effector functions exploiting human immune system, such as antibody-dependent cellular cytotoxicity, particularly for IgG1 isotype (1,2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of them are now under various phases of clinical trials (1)(2)(3)10). The advantages of agonistic mAbs compared with TRAIL include specificity of binding to their target receptor without cross-reactivity with the DcRs, much longer serum half-life, and the crystallizable fragment (Fc)-mediated effector functions exploiting human immune system, such as antibody-dependent cellular cytotoxicity, particularly for IgG1 isotype (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the cognate ligand of recombinant TRAIL, several agonistic monoclonal antibodies (mAb) have been developed by targeting DR4 (7)(8)(9)(10) or DR5 (11)(12)(13)(14)(15)(16), which also induce cell death in various types of tumors in vitro and in vivo. Some of them are now under various phases of clinical trials (1)(2)(3)10).…”
Section: Introductionmentioning
confidence: 99%
“…This clinical failure has been subsequently attributed to the low in vivo bioactivity of the TRAIL molecules administered, and their rather short terminal plasma half-life (»1 hour). 4,6 Consequently, alternative therapeutic strategies targeting TRAIL death receptors have been developed, such as agonistic monoclonal antibodies directed against either DR4, e.g., mapatumumab, 8,9 or DR5, e.g., conatumumab 10 and lexatumumab. 11 However, Phase 1 and 2 clinical studies revealed ambiguous results (for review see refs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, no immunogenicity against mapatumumab or lexatumumab has been observed. Clinical responses ranging from stable disease, partial responses and even a complete response have been reported after administering either untagged versions of recombinant human TRAIL or antibodies targeting death receptors as monotherapy (Plummer et al, 2007;Tolcher et al, 2007;Greco et al, 2008;Hotte et al, 2008;Leong et al, 2009;Mom et al, 2009;Trarbach et al, 2010;Wakelee et al, 2010). Taken together, safety results and clinical responses encourage further diseasedirected assays of these agents.…”
Section: Novel Paradigms For Cancer Therapy V Pavet Et Almentioning
confidence: 99%